2012
DOI: 10.1007/s00268-012-1477-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival Rates for Abdominal Aortic Aneurysm Treatment Methods

Abstract: Patients treated successfully for AAA have the same relative long-term survival as the general population. The time required to reach the same survival, however, differs between the treatment groups and is longest in the group with a rAAA. The variable survival rates should be taken into consideration when treating patients with an AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Twenty-four studies, consisting of 40 study arms, provided mean age data and were included in this analysis. 3,5,12,13,1517,21,23,24,26,27,29,31,32,35,3742,44,45 This comprised 103,021 patients with a mean age range of 63 years to 78.5 years, from data covering the period 1978–2011 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies, consisting of 40 study arms, provided mean age data and were included in this analysis. 3,5,12,13,1517,21,23,24,26,27,29,31,32,35,3742,44,45 This comprised 103,021 patients with a mean age range of 63 years to 78.5 years, from data covering the period 1978–2011 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In general, many of the current devices used according to instructions for use are equivalent regarding postoperative complications, migration, and aneurysm-related mortality [25]. In addition to device design, we have an active interest in studying the outcomes following AAA repair [26]. Recently, we compared the relative survival rates of patients after various operative treatments for AAA to those of the general population.…”
Section: Clinical Studies On Aaamentioning
confidence: 99%
“…Kaplan-Meier curves were generated with the indicated numbers of patients at risk. Reproduced with permission from [26]. …”
Section: Figurementioning
confidence: 99%
“…Recent studies have shown 1-year survival rates of 57-89.1 % for patients treated with chimney technique and of 85-93 % for patients treated with fenestrated endografts, and 5-year survival rates of 60 % for patients treated with fenestrated endografts [21][22][23]. For elective open aneurysm repair, reported survival rates at 1 year are 73-89 % and at 5-6 years 69.9-84.5 % [2, [24][25][26]. In our study, we only included patients who had follow-up imaging after 6 months or more; however, in a previous study our group assessed mortality rate in patients electively treated with VORTEC as part of the hybrid procedure, which has shown to be 8.6 % in 30 days and 25.8 % during a mean follow-up of 22.1 months.…”
Section: Discussionmentioning
confidence: 99%